Emphysematous Cholecystitis in 24-Year-old Male Without Predisposing Factors - Sayit, Asli Tanrivermis (J Clin Diagn Res, 2015)
Emphysematous cholecystitis (EC) is a life threatening condition characterized by gangrene of the gallbladder due to an infection with gas-forming organisms. It is more common in elderly men and has been associated with systemic disease, especially diabetes and vascular disease. Computed tomography is the most important and accurate imaging modality for the diagnosis of EC. EC should be thought of when the radiographic presence of gas is detected within the gallbladder wall or lumen. Emergency surgical intervention and antibiotic treatment for the gas-forming organism should be initiated after the diagnosis of the EC. Here, we present the imaging and pathologic findings of a 24-year-old male with EC without any predisposing factors, successfully treated with laparoscopic cholecystectomy.